Analisis Peranan Sistem Penagihan Piutang Negara Dalam Meningkatkan Efektifitas Kinerja pada Kantor Wilayah Direktoriat Jendral Keuangan Negara Medan - Masrida, Masrida; Nasution, Juliana (Lembaga Riset Ilmiah, Yayasan Mentari Meraki Asa, 2022)
In managing state assets, the Ministry of Finance establishes the Directoeate General of State Assets (DJKN). Based on the Regulation of the Minister of Finance Number 206/PKM,01/2014 concerning the Organization and Work Procedure of the Ministry of Financ,the Directorate General of State Assets has the task of formulating and implementing policies and technical standardization in the fileds of state assets, state receivables and auctions. The purpose of this study was to analyze andd test the suitability of the procedure for submitting state receivables to the procedure for paying off state receivable and to find out how the role of the state receivable collection system in increasing the effectiveness of performance at the North Sumatra DJKN regional Office, with the Regulation of the Minister of Finance Number 240/PKM.06/2016. The analytical method used in this study is a descriptive method which begins with collecting data to be abalyzed then a conclusion is drawn and the type of research used is descriptive qualitative. The results of of the study showed. The purpose of this study was to analyze and test the suitability ofthe procedure for that the role system for collecting state receivables was carried out in accordance with the Regulation of the Minister og Finance Number 240/PKM.06.2016